2016
DOI: 10.1155/2016/2842969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crushed Glass Cullet Sizes on Physical and Mechanical Properties of Red Clay Bricks

Abstract: This study reports the effect of clear waste glass from bottles added on 20 to 30 wt.% and variable particle size (<500, <300, and <212 μm), into clay mixtures for the handmade brick manufacturing process. The bricks were manufactured with mixtures of clay, crushed glass, and water in different proportions, homogenized, casted in wooden molds, air-dried at room temperature for 72 h, and sintered at 1000°C for 12 h. Total shrinkage, water absorption, compressive strength, microstructure, and phase comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…That is to say, the larger the amount of the added TFT-LCD waste glass powder, the higher the density of the resulting bricks. This is due to the waste glass particles fusing with the clay bodies, which contributed to the densification of the brick [40]. On the other hand, the results of the ANOVA of density are given in Table 8.…”
Section: Densitymentioning
confidence: 99%
See 3 more Smart Citations
“…That is to say, the larger the amount of the added TFT-LCD waste glass powder, the higher the density of the resulting bricks. This is due to the waste glass particles fusing with the clay bodies, which contributed to the densification of the brick [40]. On the other hand, the results of the ANOVA of density are given in Table 8.…”
Section: Densitymentioning
confidence: 99%
“…Further, the larger the amount of the added TFT-LCD waste glass powder, the lower the water absorption of the resulting bricks. The reason for this is that increasing the cullet content promoted the formation of the liquid phase of glass, which contributed to the densification of the bricks, thereby reducing the water absorption [40]. The results of the ANOVA of water absorption are given in Table 10.…”
Section: Water Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was attributed to the re-vitrification of glass particles during high-temperature firing [27]. Additionally, some researchers found that glass waste had the potential to reduce the required temperature for the sintering process because of the presence of sodium oxide and calcium oxide in the glass [29,30]. Moreover, due to the extremely high temperature triggering the crystalline restructuring, fired bricks become a desirable article to immobilize the glass waste containing hazardous substances [2,24,31].…”
Section: Introductionmentioning
confidence: 99%